Phytochemical Screening, Antibacterial and Cytotoxic Activities of Petroselinum Crispum Leaves Grown in Oman: Antibacterial and cytotoxic activities of petroselinum crispum from Oman - Al-Marwa H. Al-Hadi,; Samiya. S. Al Rahbi,; Md Sohail Akhtar,; Sadri Said,; Afaf Weli,; Qasim Al-Riyami, (Iranian Journal of Pharmaceutical Sciences, 2024)
Petroselinum crispum belongs to the Apiaceae family, is a well-known spice and vegetable. The essential oil obtained from the fruit has also strong action on the central nervous system. Present study is designed to evaluate the phytochemical screening, antibacterial and cytotoxic activity of the leaves of Petroselinum crispum collected from Oman. Results of phytochemical screening indicate the presence of primary and secondary metabolites. Antimicrobial activity was measured using disc diffusion method against S.aureus,E.coli, P.aeruginosa and K. pneumonia. Brine shrimp test was used to estimate cytotoxic activity. In antibacterial assay, Petroselinum crispum leaves extracts showed very strong results, inhibition zones ranged from 7 – 20 mm. So this plant can be used as a good source of potential antimicrobial agent. Hydro alcoholic and Petroleum ether extracts showed the highest antibacterial activity. Furthermore, Ethyl acetate and Hydro alcoholic extracts have almost killed 90% of the shrimp larvae at higher concentration of 1000 μg/ml. LC50 values for the two extracts was 51.95 and 88.15μg/ml, respectively. Non polar fractions like chloroform extract have displayed low cytotoxic activities as compare to polar extracts.